1993
DOI: 10.1093/carcin/14.12.2495
|View full text |Cite
|
Sign up to set email alerts
|

Elevated 8-hydroxydeoxyguanosine in hepatic DNA of rats following exposure to peroxisome proliferators: relationship to carcinogenesis and nuclear localization

Abstract: Increased oxidative DNA damage due to increased peroxisomal generation of H2O2 is a potential mechanism in the carcinogenicity of chemical peroxisome proliferators (PP) in rodent liver. In order to determine the relationship between carcinogenicity and peroxisome-dependent DNA damage, levels of DNA base oxidation were examined by comparing 8-hydroxydeoxyguanosine (8-OHdG) in DNA from unfractionated liver of male F344 rats following dietary exposure to PP [WY-14,643, 0.1% or 0.005%; di(2-ethylhexyl)phthalate (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…Induction of significant and high steady levels of 8-OHdGs essentially plays a critical role for the activation of carcinogenic properties of cells [Floyd, 1990;Cattley and Glover, 1993;Shen et al, 1995]. Using the sensitive HPLC-ECD method, we detected here a substantial level of 8-OHdGs in hepatic DNA of rats treated with DEN over the vehicle control that supported this concept.…”
Section: Discussionsupporting
confidence: 70%
“…Induction of significant and high steady levels of 8-OHdGs essentially plays a critical role for the activation of carcinogenic properties of cells [Floyd, 1990;Cattley and Glover, 1993;Shen et al, 1995]. Using the sensitive HPLC-ECD method, we detected here a substantial level of 8-OHdGs in hepatic DNA of rats treated with DEN over the vehicle control that supported this concept.…”
Section: Discussionsupporting
confidence: 70%
“…A number of indirect confirmations for DEHP-initiated increases in oxidants have been collected over past two decades [120,121,122,123,124,125]. It should be noted, however, that causative relevance of some of such evidence to the carcinogenic effect of PP in general, and DEHP in particular, has been questioned and contrasting views have been presented [126,127,128,129,130]. It has been shown that PPARα is required for generation of oxidants in mouse liver after prolonged [weeks, [131]], but not acute [hours, [132]] exposure to PPs.…”
Section: Production Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…While these two processes together may largely explain the mechanism of the carcinogenic response [Reddy and Lalwani, 1983;Doull et al, 1999], some research indicates that there may be other important factors such as indirect genotoxicity; effects on cell transformation and intercellular communication; and other non-peroxisomal parameters such as mitrochondrial effects and effects on enzyme activity [Cattley and Glover, 1993;Melnick and Cohen, 1996;Gonzalez et al, 1998;KemI, 1999]. For example, DEHP and diethylhexyl adipate, which result in similar levels of peroxisomal induction in rats do not lead to similar tumogenic responses [Melnick and Kohn, 1996].…”
Section: Mechanisms Of Carcinogenesis and Other Effectsmentioning
confidence: 99%